Model Analysis Of The Influence Of Assets, Debt, And Equity On Financial Performance With Sales And Profit As Intervening Variables In Food & Staples Retailing Sector Companies On The Indonesia Stock Exchange - Yunan Surono (Information Technology and Science (ITScience), 2025)
The research aims to identify and analyze the model of the influence of the variables of assets, debt, and equity on financial performance, with sales and profit as intervening variables in companies in food & staples retailing sector listed on the Indonesia Stock Exchange during the period 2018 - 2023. Data, facts, and information were obtained from the Indonesia Stock Exchange and the financial reports of each issuer in the food & staples retailing sector during the study period, which showed fluctuations and significant differences in values throughout the research period. The data analysis for the research used Partial Least Square (PLS-SEM), with Smart PLS 4.0 software. The research results indicate 1) The asset variable significantly affects the financial performance variable of food & staples retailing companies on the Indonesia Stock Exchange during the period 2018 - 2023. 2) The asset variable significantly affects the profit variable. 3) The asset variable significantly affects the sales variable. 4) The debt variable does not affect the financial performance variable. 5) The debt variable does not affect the profit variable. 6) The debt variable does not affect the sales variable. 7) The equity variable does not affect the financial performance variable. 8) The equity variable does not affect the profit variable. 9) The equity variable does not affect the sales variable. 10) The sales variable significantly affects the financial performance variable. 11) The profit variable does not affect the financial performance variable. 12) The asset variable significantly affects the financial performance variable through the sales variable. 13) The asset variable does not affect the financial performance variable through the profit variable. 14) The debt variable does not affect the financial performance variable through the sales variable. 15) The debt variable does not affect the financial performance variable through the profit variable. 16) The capital variable does not affect the financial performance variable through the sales variable. 17) The capital variable does not affect the financial performance variable through the profit variable